Simplify #3:

[cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx]
= [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx]
= [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx]
= [cosx-cosxsinx]/[cosx+cosxtanx]
= [cosx(1-sinx]/[cosx(1+tanx]
= (1-sinx)/(1+tanx)

Is this correct???

1 answer

looks good to me
Similar Questions
  1. Trigonometric IdentitiesProve: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx +
    1. answers icon 0 answers
  2. Proving identity(sinx+tanx)/(cosx+1)=tanx RS: (sinx+(sinx/cosx))/(cosx+1) ((sinxcosx/cosx)+(sinx/cosx))x 1/(cosx+1)
    1. answers icon 1 answer
  3. Verify the identity:tanx(cos2x) = sin2x - tanx Left Side = (sinx/cosx)(2cos^2 x -1) =sinx(2cos^2 x - 1)/cosx Right Side = 2sinx
    1. answers icon 0 answers
  4. tanx+secx=2cosx(sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx multiplying both sides by cosx sinx + 1 =2cos^2x sinx+1 =
    1. answers icon 0 answers
more similar questions